How Molecular Chiralities of Bis(mandelato)borate Anions Affect Their Binding Structures With Alkali Metal Ions and Microstructural Properties in Tetraalkylphosphonium Ionic Liquids - Pei, Han-Wen; Li, Bin; Laaksonen, Aatto; Wang, Yong-Lei (Frontiers in Chemistry, 2020)
Spiroborate anions based inorganic electrolytes and ionic liquids (ILs) have fascinating electrochemical and tribological properties, and have received widespread attention in industrial applications. Molecular chiralities of spiroborate anions have a significant effect on microstructures and macroscopic functionalities of these ionic materials in applications, and thus deserve a fundamental understanding. In current work, we performed quantum chemistry calculations to address binding strength and coordination structures of chiral bis(mandelato)borate ([BMB]) anions with representative alkali metal ions. The optimized [BMB] conformers are categorized into V-shaped, bent, and twisted anion structures with varied electrostatic potential contours, conformational energies, and distinct alkali metal ion-[BMB] binding structures. Alkali metal ions have additional associations with phenyl groups in V-shaped [BMB] conformers owing to preferential cation-$π$ interactions. Furthermore, effects of molecular chiralities of [BMB] anions on thermodynamics and microstructural properties of tetraalkylphosphonium [BMB] ILs were studied by performing extensive atomistic interactions. Oxygen atoms in [BMB] anions have competitive hydrogen bonding interactions with hydrogen atoms in cations depending on molecular chiralities and steric hindrance effects of [BMB] anions. However, molecular chiralities of [BMB] anions have negligible effect on liquid densities of tetraalkylphosphonium [BMB] ILs and spatial distributions of boron atoms in anions around phosphorous atoms in cations. Enlarging tetraalkylphosphonium cation sizes leads to enhanced cation-anion intermolecular hydrogen bonding and Coulombic interactions due to enhanced segregation of polar groups in apolar networks in heterogeneous IL matrices.